Perlindungan Hukum Bagi Pencipta Atau Pemegang Hak Cipta Yang Ciptaannya Digunakan Sebagai Ringtone - Rory Jeff Akyuwen; Wijaya Natalia Panjaitan (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Law Number 18 of 2014 is one of the products of the law which regulates the authority and rights of creators for their creations. Specifically for music copyrights or hits related to the illegal sale of ringtones or ringtones that use songs belonging to the creators. This is of course detrimental to the creator and is a violation of copyright.Purposes of the Research: The aim is to balance the rights and obligations between creators or copyright holders and those who want to use them for commercial purposes.Methods of the Research: This writing uses a normative juridical research method, the legal materials used are secondary legal materials obtained through library research on primary, secondary and tertiary legal materials. Legal materials are discussed with a statutory approach, a concept approach and a case approach.Results of the Research: That in principle the process of proving criminal cases conducted online can be accepted according to the Criminal Procedure Code as an effort to fill the legal vacuum in the case of "certain circumstances" which are determined as emergencies or other circumstances. Whereas a criminal case evidence is said to be ideal, both in direct/normal trial and electronic/online trial, if it has fulfilled the evidentiary parameters, namely: implementation of proof principles/theory; evidence; submission of evidence; burden of proof; power of proof; and minimal evidence.